2014
DOI: 10.3892/ol.2014.2451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor-β1 on the proliferation and invasion of the HTR-8/SVneo cell line

Abstract: Transforming growth factor-β1 (TGF-β1) is involved in the regulation of trophoblast cell proliferation and invasion. However, the mechanism underlying this process remains unknown, which is predominantly due to the difficulty in obtaining and maintaining primary trophoblast cells in culture over a long period of time. The HTR-8/SVneo cell line is an immortalized trophoblast cell line, which has been reported to exhibit a number of similar characteristics to those of parental trophoblast cells. Therefore, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…For instance, productions of TGF-β and Nodal, as well as their receptors, were significantly enhanced in PE placentas, which may lead to over-activated signaling, excessive cell apoptosis, and less invasion. 20 , 21 , 40 More importantly, in human placenta, TGF-β primarily regulates trophoblast cell invasion, 22 , 23 , 24 , 25 , 26 , 27 and Nodal promotes cell apoptosis. 41 We found that miR-18a increased cell invasiveness ( Figures 6 C and 6D) but did not influence the cell growth or cell cycle ( Figures 6 E and 6F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, productions of TGF-β and Nodal, as well as their receptors, were significantly enhanced in PE placentas, which may lead to over-activated signaling, excessive cell apoptosis, and less invasion. 20 , 21 , 40 More importantly, in human placenta, TGF-β primarily regulates trophoblast cell invasion, 22 , 23 , 24 , 25 , 26 , 27 and Nodal promotes cell apoptosis. 41 We found that miR-18a increased cell invasiveness ( Figures 6 C and 6D) but did not influence the cell growth or cell cycle ( Figures 6 E and 6F).…”
Section: Discussionmentioning
confidence: 99%
“… 19 Furthermore, it is highly expressed in PE placentas, 20 , 21 and the dysregulation of its signaling pathway is responsible for the dysfunction of trophoblast cells and the pathophysiology of PE. 21 , 22 , 23 , 24 , 25 , 26 , 27 We therefore speculated that miR-18a interferes with the TGF-β signaling in PE placentas via targeting Smad2 and/or Smad3.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we isolated three different human MSC lines from Wharton's jelly of umbilical cord tissue of three female neonates and examined the effects of these hUCMSCs on the cellular functions of trophoblast cells. HTR-8/SVneo is an immortalized trophoblast cell line and is usually used to study villous trophoblast cells [ 15 17 ]. We thus used the HTR-8/SVneo cell line as a model to explore the influence of hUCMSCs on proliferation, migration, invasion, and secretion functions of trophoblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β activates TGF-β receptor (TβR)I and TβRII, resulting in the phosphorylation of receptor-regulated SMAD2/3, which is associated with the common mediator SMAD4. The SMAD2/3/4 complex is translocated to the nucleus, where it binds to DNA and regulates the transcription of several genes (31,32). Increased mRNA and protein expression levels of SMAD3 and SMAD4 promote cell proliferation, migration and invasion (33).…”
Section: Discussionmentioning
confidence: 99%